A remarkable new species of Teledapus Pascoe, 1871 from China (Coleoptera: Cerambycidae: Lepturinae: Teledapini) - Huang, Gui-Qiang; Li, Song; Zhang, Gui-Mei (Zootaxa, 2021)
Teledapus linyejiei sp. nov. is described from Yunnan, China and its adult habitus, hind wings and terminalia are described and illustrated.